1994
DOI: 10.1037/0096-3445.123.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of truncation on reaction time analysis.

Abstract: Many reaction time (RT) researchers truncate their data sets, excluding as spurious all RTs falling outside a prespecified range. Such truncation can introduce bias because extreme but valid RTs may be excluded. This article examines biasing effects of truncation under various assumptions about the underlying distributions of valid and spurious RTs. For the mean, median, standard deviation, and skewness of RT, truncation bias is larger than some often-studied experimental effects. Truncation can also seriously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
294
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(298 citation statements)
references
References 49 publications
1
294
0
3
Order By: Relevance
“…However, because our goal requires measures of detection and of reaction thresholds that are as comparable as possible, we used the 0.561 quantile rather than the median. The mean RT may also be a good measure of the location of an RT distribution, although it has the disadvantage of being very sensitive to Boutliers,p articularly to late reactions (see Ulrich and Miller 1994). However, a mean cannot be computed from all trials when there are misses.…”
Section: Discussionmentioning
confidence: 99%
“…However, because our goal requires measures of detection and of reaction thresholds that are as comparable as possible, we used the 0.561 quantile rather than the median. The mean RT may also be a good measure of the location of an RT distribution, although it has the disadvantage of being very sensitive to Boutliers,p articularly to late reactions (see Ulrich and Miller 1994). However, a mean cannot be computed from all trials when there are misses.…”
Section: Discussionmentioning
confidence: 99%
“…"The median, however, is inappropriate for this purpose because it is not, in general, additive" (see Sternberg, 1969, p. 286). Our main hypothesis is concerned with the examination of linear relations between RT and memory load for which Ulrich and Miller (1994) showed that "using truncated RTs can seriously distort linear relations between RT and an independent variable" (p. 34). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Resultsmentioning
confidence: 99%
“…prior to analysis erroneous responses were excluded and an inverse transformation was used to reduce the effect of remaining outliers (see Ratcliff, 1993;Ulrich & Miller, 1994). For the Stop Signal Reaction Time task, SSRTs were estimated using the mean method (mean of inhibition function subtracted from the mean of RT distribution) as outlined by Band et al (2003) and Verbruggen and Logan (2009).…”
Section: Preliminary Analysesmentioning
confidence: 99%